Implementation of automatic sensors for continuous monitoring of runoff quantity and quality in small catchments - Linjama, Jarmo; Puustinen, Markku; Koskiaho, Jari; Tattari, Sirkka; Kotilainen, Helmi; Granlund, Kirsti (MTT Agrifood Research Finland, 2009)
Lewis, J. 1996. Turbidity-controlled suspended sediment sampling for runoff-even load estimation. Water Resources research 32: 2299 2310. Mustonen, S. 1965. Hydrologic investigations by the Board of Agriculture during the years 1957 to 1964. Helsinki. 144 p. Puustinen M, Koskiaho J. & Peltonen K. 2005. Influence of cultivation methods on suspended solids and phosphorus concentrations in surface runoff on clayey sloped fields in boreal climate. Agriculture, Ecosystems and Environment 105: 565 579. Puustinen, M., Tattari, S., Koskiaho, J. & Linjama, J. 2007. Influence of seasonal and annual hydrological variations on erosion and phosphorus transport from arable areas in Finland. Soil & Tillage Research 93: 44 55. Rekolainen, S. 1993. Assessment and mitigation of agricultural water pollution. Publications of the Water and Environment Research Institute 12. National Board of Waters and Environment, Helsinki, Finland. 34 p. Seuna, P. 1983. Small basins a tool in scientific and operational hydrology. Publications of the Water Research Institute 51. National Board of Waters, Finland. 61 p. Turtola, E. 1999. Phosphorus losses in surface runoff and drainage water affected by cultivation practices. Academic Dissertation. University of Helsinki. 47 p. Valkama, P., Lahti, K. & Särkelä, A., 2007. Automated water quality monitoring in the river Lepsämänjoki. Terra 119: 195 206. Vehviläinen, B. & Huttunen, M. 2002. The Finnish watershed simulation and forecasting system (WSFS). Proceedings of the XXIst Conference of the Danubian countries on the hydrological forecasting and hydrological bases of water management. Bucharest-Romania. 2 6 September 2002. Vuorenmaa, J., Rekolainen, S., Lepistö, A., Kenttämies, K. & Kauppila, P., 2002. Losses of nitrogen and phosphorus from agricultural and forest areas in Finland during the 1980s and 1990s. Environmental Monitoring and Assessment. 76: 213 248. SELOSTUS Jatkuvatoimisten antureiden soveltuvuus veden määrän ja laadun seurantaan pienillä valuma-alueilla Jarmo Linjama, Markku Puustinen, Jari Koskiaho, Sirkka Tattari, Helmi Kotilainen ja Kirsti Granlund Suomen ympäristökeskus Automaattisten antureiden viimeaikainen kehittyminen on avannut uusia mahdollisuuksia pienten valuma-alueiden monitorointiin. Tässä tutkimuksessa kymmenien vuosien ajan seuratulle valuma-alueelle, Savijoelle, asennettiin sameus- ja nitraattianturi ja tehtiin kuormituslaskenta sekä antureiden tulosten perusteella että perinteiseen harvaan näytteenottoon perustuvin menetelmin. Huomiota kiinnitettiin erityisesti laitteiden asentamiseen ja antureiden kalibrointiin. Huolellisen asentamisen jälkeen laitteet toimivat vuoden mittaisen havaintojakson ajan teknisesti moitteettomasti. Sameuden ja nitraattikäyrien kalibrointi vesinäytteiden perusteella osoitti, että vesinäytteiden ja anturidatan vastaavuus on erittäin hyvä. Alustavien tulosten mukaan perinteiseen seurantaan perustuva kuormitusarvio ei ole yksittäisten vuosien osalta kovin luotettava. Tämän tutkimuksen seurantavuosi oli kuitenkin poikkeuksellinen useiden talviaikaisten valuntapiikkien vuoksi, joita harvan, perinteisen seurannan vesinäytteet eivät olisi tavoittaneet. Tässä esitettyä automaattiantureiden ja vesinäytteiden tuloksiin perustuvaa kuormituslukujen vertailua ei voida yleistää. Tulos kuitenkin osoittaa, että tämänkaltaista monitorointia on tärkeä jatkaa ja laajentaa. Jatkotutkimuksissa huomiota tulee kiinnittää laskentamenetelmien kehittämiseen, erityisesti siihen, kuinka anturiaineistosta päästään mahdollisimman yksinkertaisesti luotettaviin kuormitusarvioihin. Ilmaston muuttuessa valuma-alueiden seuranta ja kuormitusarviointi ovat todennäköisesti entistä vaativampia ja maatalouden vesiensuojelutoimenpiteiden vaikutusten havaitseminen myös entistä haasteellisempaa.

Development of new automatic sensor-based techniques has expanded the possibilities for intensive monitoring of water quality in small catchments. In this study turbidity and concentration of nitrate-N were monitored with probes in the Savijoki catchment, which has been observed with traditional methods for decades. Particular attention was paid to implementation of the equipment, calibration of the probes and calculation methods. All equipment functioned technically well during the one year monitoring period. Calibration of turbidity and nitrate-N proved that the sampled values agree well with the probe results. However, it seems that loading estimates made with the traditional method are not very reliable for individual years. The research period in this study was exceptional with its many runoff peaks in winter. It is not possible to catch the peaks with traditional monitoring, why the results and comparisons between automatic probes and traditional monitoring cannot be generalized. However, the results proved that novel monitoring techniques have to be continued and extended. In further studies the calculation methods need developed and improved to be to get reliable loading estimations from the sensor data as simply as possible. In a changing climate, the monitoring, loading estimations, and consequently the assessment of the effect of agricultural water protection measures will probably turn even more difficult and challenging.
Keywords: Ys; Ka; monitoring; probes; turbidity; nitrate; agriculture; catchments; runoff; erosion; phosphorus